Pendekatan Keunggulan Kompetitif dalam Mewujudkan Pertumbuhan Bisnis yang Berkelanjutan - Cahyatih Kumandang; Eri Kusnanto; Forme Onray Siallagan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Sustainable business growth has become a primary focus for companies worldwide in facing global economic challenges and rapidly changing markets. The 82nd National Seminar of STIE Kasih Bangsa explored strategies to achieve sustainable business growth through competitive advantage. The webinar highlighted the importance of adapting to market changes, operational efficiency, innovation, networking, and teamwork in achieving competitive advantage. The discussion results indicate that companies need to invest in technology and innovation, understand market trends, and build strong relationships with stakeholders to maintain competitiveness in the global market. Additionally, the role of angel investors and wise investment strategies are also crucial factors in supporting business growth, especially for startups. This webinar provides valuable insights into the importance of flexible and adaptive strategies in achieving sustainable business growth.